Impact of intrinsic backbone chain stiffness on the morphologies of bottle-brush diblock copolymers. (5th August 2016) - Chremos, Alexandros; Theodorakis, Panagiotis E.
Abstract: Self-assembly methods are used for the production of photonic and nanoporous materials derived from block copolymers. In this context, bottle-brush copolymers have demonstrated a number of advantages over the respective linear copolymers, such as faster self-assembly kinetics and a richer morphology behavior. However, the effect of intrinsic molecular stiffness on the morphology of bottle-brush copolymers has been previously overlooked. Here, we investigate the role of the intrinsic backbone chain stiffness on the morphology behavior of bottle-brush diblock copolymers by using molecular dynamics simulations of a bead-spring coarse-grained model. We focus on bottle-brush macromolecules having blocks of the same volume fraction and asymmetric-in-length side chains. We find that an increase of the backbone stiffness triggers an order–order transition from hexagonal packed cylinders to lamellar morphologies with asymmetric domain spacings, which is of particular interest for the manufacturing of nanopatterning and semiconductor applications. The change in the morphology is due to the effective many-body attractions between the blocks resulting in a parallel stacking that disrupts the symmetry of the cylindrical morphology. We anticipate that our work will underline the significance of intrinsic molecular stiffness in the self-assembly of polymer systems, which has been previously neglected. Graphical abstract: Highlights: Increase of backbone stiffness in bottle-brush copolymers leads to cylinder-lamellar transition. Increased backbone stiffness causes orientational ordering of the backbones. Bottle-brush copolymers can create morphologies with asymmetric lamellar domains.